Dual Axis Solar Tracking System for Solar Panel - Purnima Singh; Roop Pahuja; Meghavi Karwasra; Sunita Beniwal; Meenakshi Bansal; Anamika Dadhich (Institute of Advanced Engineering and Science, 2016)
Sustainable energy systems are necessary for the economic growth and a healthy environment. India is currently suffering from an economic slump and acute fuel shortage. To overcome these issues the use of renewable energy resources needs to be enhanced manifold. The main purpose of this paper is to present a tracking system which will cause better alignment of solar panel with sunlight and to harvest solar power. The proposed system changes its direction in two axis to trace the coordinate of sunlight by detecting change in light intensity through light dependent resistors. Hardware testing of the proposed system is done for checking the system ability to track and follow the sunlight in an efficient way. Dual axis solar tracking system superiority over stationary solar panel is also presented.